Ranah Afektif Dalam Evaluasi Pendidikan Agama Islam, Penting Tapi Sering Terabaikan - Ahmad Darmadji (Islamic University of Indonesia, 2014)
This paper discusses the neglectedness of affective aspect on study evaluation of Islamic Religion Education course (Pendidikan Agama Islam) at higher education institution. It is found that the neglectedness of affective aspect is caused by some critical factors: 1) different perspective among scholars on what aspect of affection that cannot be measured, for example: faith; 2) the learning objective of Islamic Religion Education course is too ideal, that make it difficult to measure; 3) vast majority of Islamic Religion Education lecturer are unable to develop good teaching instruments which cover affective aspect; and 4) the students-lecturers ratio are too wide and far from ideal. To solve this problem, some suggestions are proposed; strengthening the good understanding of affective aspect on Islamic Religion Education among lecturers; and enriching evaluation design and model to reveal affective aspect of students.